2010
DOI: 10.5138/ijdd.2010.0975.0215.02023
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, evaluation and optimization of stomach specific in situ gel of clarithromycin and metronidazole benzoate.

Abstract: The present investigation deals with the formulation, optimization and evaluation of sodium alginate based In situ gel of Clarithromycin and Metronidazole Benzoate. Sodium alginate used as a polymer and CaCO 3 was used as a cross-linking agent. The In situ formulation exhibited well, viscosity, drug content and sustained drug release; this study reports that oral administration of aqueous solutions containing sodium alginate results in formation of In situ gel, such formulations are homogenous liquid when admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The gelation involves formation of double helical junction zone followed by aggregation of the double helical segments to form a three dimensional network by complexation with Ca +2 ions and hydrogen bonding with water. 27 It was observed that all formulations showed immediate gelation on contact with acidic environment and retained gel structure for more than 12 h. The rigidity of the gel confers controlled release property to the formulation as the drug molecules have to traverse through the complex network of polymer chains to reach the physiological environment.…”
Section: In Vitro Gelling Capacitymentioning
confidence: 96%
“…The gelation involves formation of double helical junction zone followed by aggregation of the double helical segments to form a three dimensional network by complexation with Ca +2 ions and hydrogen bonding with water. 27 It was observed that all formulations showed immediate gelation on contact with acidic environment and retained gel structure for more than 12 h. The rigidity of the gel confers controlled release property to the formulation as the drug molecules have to traverse through the complex network of polymer chains to reach the physiological environment.…”
Section: In Vitro Gelling Capacitymentioning
confidence: 96%
“…Accurately weighed solids were used to make the formulations as per the method described elsewhere 8,14 . Accordingly, in about 30 ml of deionized water, HPMC K4M was allowed to hydrate overnight.…”
Section: Methods: Preparation Of In Situ Gelling Formulationsmentioning
confidence: 99%
“…These systems can sustain drug release, improve bioavailability, reduce dosing frequency and improve patient acceptability 4,5 . These systems have been investigated for the gastric delivery of amoxicillin 6 , clarithromycin 7 , metronidazole 8 , acetohydroxamic acid 9 , and levofloxacin hemihydrates 10 for eradication of Helicobacter pylori (H. pylori) and showed significant anti-H.pylori effect than the conventional dosage forms.…”
mentioning
confidence: 99%
“…In vitro Floating Study 28 The in vitro floating study was carried out using USP dissolution apparatus II having 500 ml of 0.1N HCl (pH 1.2) .The medium temperature was kept at 37 o C. Accurately weighed 10 mL of the prepared in situ gel formulations were drawn up using disposable syringe and placed into the Petridis (4.5 mm internal diameter) and finally the Petridis containing the formulation was kept in the dissolution vessel containing medium without much disturbance. The time the formulation took to emerge on to the medium surface (Floating Lag Time) and the time over which the formulation constantly floated on the dissolution medium surface Duration of Floating) were noted.…”
Section: 27mentioning
confidence: 99%